"An Unusual Urological Tumour": Above the Collar and below the Belt. (29th September 2012) - Mayer, Erik K.; Undre, Shabnam; Cohen, Daniel C.; Walker, Marjorie M.; Vale, Justin A.; Patel, Anup
Abstract : Bladder lymphomas are rarely primary tumours and more commonly associated with systemic lymphoma, either as nonlocalised bladder lymphoma or as secondary bladder lymphoma. Primary bladder lymphomas (PBL) tend to be low-grade mucosa-associated lymphoid tissue (MALT) type, contrasting with diffuse large cell or follicular centre cell types more commonly seen in secondary bladder lymphoma. Bladder involvement by systemic lymphoma infers poor prognosis and patients often have no localising symptoms (typically a postmortem diagnosis). Other treatments are preferred over surgery for all bladder lymphomas, except where diagnosis is uncertain or for relief of irritative bladder symptoms. We describe a unique case of systemic high-grade B-cell lymphoma with simultaneous cutaneous renal and bladder lesions at presentation.